2012
DOI: 10.1186/1747-597x-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expertise on football betting

Abstract: BackgroundFootball (soccer) is one of the most popular sports in the world, including Europe. It is associated with important betting activities. A common belief, widely spread among those who participate in gambling activities, is that knowledge and expertise on football lead to better prediction skills for match outcomes. If unfounded, however, this belief should be considered as a form of “illusion of control.” The aim of this study was to examine whether football experts are better than nonexperts at predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Zudem machte sich der Skill-Einfluss in der Gesamtbetrachtung nicht auf finanzieller Ebene bemerkbar. Khazaal et al [21] führte auf der Grundlage von Tipps auf Fußballspiele der Europameisterschaft 2008 logistische Regressionsanalysen durch (kontrolliert für Alter und Geschlecht). Die Befunde zeigten, dass zwischen der Vorhersage des exakten Ergebnisses und der Gruppenzugehörigkeit -unterteilt nach ExpertInnen, Amateuren und Laien -keine statistische Assoziation bestand.…”
Section: Einschlusskriterienunclassified
“…Zudem machte sich der Skill-Einfluss in der Gesamtbetrachtung nicht auf finanzieller Ebene bemerkbar. Khazaal et al [21] führte auf der Grundlage von Tipps auf Fußballspiele der Europameisterschaft 2008 logistische Regressionsanalysen durch (kontrolliert für Alter und Geschlecht). Die Befunde zeigten, dass zwischen der Vorhersage des exakten Ergebnisses und der Gruppenzugehörigkeit -unterteilt nach ExpertInnen, Amateuren und Laien -keine statistische Assoziation bestand.…”
Section: Einschlusskriterienunclassified
“…Appropriate machine learning model choice depends on the underlying data's statistical properties. Some soccer forecasting models were developed for individual matches, which is typically accounted for by multinomial logistic regression models, given the three main outcomes of a soccer match (e.g., (Khazaal et al, 2012;Koning, 2000;Willoughby, 2002)). But the present model also forecasts bet outcomes, which depend on the specific teams' characteristics, where a conditional logistic regression is more appropriate (Smith, Paton, & Vaughan Williams, 2009).…”
Section: Model Specificationsmentioning
confidence: 99%
“…At the same time, with more intense emotional experience (Mao & Zhang, 2014), they tends to invest more time and money to buy football lottery (Gordon, Gurrieri, & Chapman, 2015), which is more likely to indulge in the lottery and lead to the problem playing. Khazaal's (2012) research found that football players who have more football skills and knowledge are more likely to have problems in football gambling.…”
Section: Introductionmentioning
confidence: 96%